Hi,

I have a question related to solving a nested summation equation with a recursive function.

Suppose I have an equation of:

So, I tried to solve this problem by using a for loop to solve the summation equation and using a recursive function to expand the order of nested summation.

` test(3,0) function [sum] = test(a,b) sum = 0; for i=1:a-b if a-b == 1 sum = 1; else sum = sum + (a-b) * test(a,b+i); end end end`

From the code I got

` ans = 9`

I appreciate any help, thanks.

## Best Answer